ANALISIS EFISIENSI INDUSTRI PERBANKAN INDONESIA DENGAN MENGGUNAKAN METODE PARAMETRIK: DISTRIBUTION FREE APPROACH - Suharyadi Suharyadi; Agus Herta Sumarto (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. This research uses the parametric method, Distribution Free Approach(DFA), by using intermediation approach to analyze the level of cost efficiency, profitefficiency, and alternative profit efficiency of the banking industry in Indonesia. Thedata used are annual report data of 89 conventional commercial banks operating for 12years (2004-2015). The result shown that the level of profit efficiency and alternativeprofit efficiency are higher than cost efficiency in the Indonesian banking industry.State-owned bank is the most efficient in cost efficiency, while the foreign bank is themost efficient in profit efficiency and alternative profit efficiency.Keyword: DFA, Cost Efficiency, Profit Efficiency, Alternative Profit Efficiency